(untitled) (Research, Society and Development, 2021)
This study reports the residence time distribution (RTD) using CO2 as tracer in Three-phase micro-packed bed (TP-mPB) reactor. Experimental measurements were obtained at the inlet and at the outlet from TP-mPB reactor using the injection of small amount (3%) of CO2 tracer inside the sweep gas current. The dynamic model characterizes a diffusion-adsorption process of CO2 tracer in terms of mass transfer phenomena (external and internal). The mathematical model was validated against a set of experimental data where simulated results of CO2 tracer adequately matched the experimental measures at the outlet of the micro-packed bed.